Show cards of the Global Physical Activity Questionnaire (GPAQ) - do they impact validity? A crossover study - Kevin Rudolf; Florian Lammer; Gerrit Stassen; Ingo Froböse; Andrea Schaller (BMC, 2020)
Abstract Background The Global Physical Activity Questionnaire (GPAQ) is applied internationally as a tool to assess the level of physical activity. The GPAQ was designed as an interview, including the use of show cards, which visualise activities of moderate and intensive physical activity and support the distinction between these intensities. The self-administered version of the GPAQ is used in the application-oriented research for reasons of economy and practicality. However, the use of show cards often remains unknown. The aim of the present study was to examine differences in validity between two self-administered versions of the GPAQ with and without show cards. Methods In this crossover study, two groups (n = 54; 57.4% female; 28.3 ± 12.2 years) received the GPAQ with or without show cards after 7 days and the respective other version after additional 7 days. For validation, all participants wore an accelerometer (ActiGraph GT3X+) on all 14 days. Differences between GPAQ versions and accelerometer data were compared by Wilcoxon signed rank test. Additionally, Spearman analyses and Bland-Altman plots were calculated. Results No statistically significant difference between the GPAQ versions could be found in regard to the accuracy of physical activity assessment (p > 0.05). Both GPAQ versions show similar correlation coefficients for vigorous physical activity (rho = 0.31-0.42) and sedentary behaviour (rho = 0.29-0.32). No statistically significant correlation was found for physical activity of moderate intensity. The Bland-Altman plots support these results, as both GPAQ versions have the same trends in terms of overestimation and underestimation of physical activity. Conclusion The use of show cards had no significant impact on questionnaire validity. Therefore, both GPAQ versions can be applied interchangeably. Nevertheless the exact description of application of the GPAQ is desirable in terms of reproducibility and transparent scientific research.